Determinant Analysis of Compliance with the Use of Mask in Wilangan Village Nganjuk Regency - Byba Melda Suhita; Devi Vinda Fransisca (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
In December 2019, the world was shocked by the outbreak of a new virus that originated in Wuhan, China and then spread rapidly to more than 216 countries and territories. The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzingthe influence of knowledge, motivation, beliefs and attitudes on the compliance of the use of masks in RW 1 Wilangan, Wilangan Village, Nganjuk Regency. The total population is 258 respondents and a sample of 158 respondents is taken by using Simple Random Sampling technique. The results showed that based on the results of Linear Regression analysis showed that the p-value 0.000 <0.05 then H1 was accepted so that it was concluded that partially there was an effect of knowledge on mask compliance, p-value 0.000 <0.05 then H1 was accepted so that it was concluded that partially there is an effect of motivation on adherence to the use of masks, p-value 0.009 <0.05 then H1 is accepted so that it is concluded that partially there is an effect of trust on adherence to the use of masks, p-value 0.001 < 0, 05 then H1 is accepted so that it is concluded that partially there is an effect of attitude on compliance with the use of masks in RW 1 Wilangan, Wilangan Village, Nganjuk Regency. And based on the results of Multiple Linear Regression analysis shows that with a p-value of 0.000 <0.05 then H1 is accepted so that it can be concluded that simultaneously there is an influence of knowledge, motivation, belief and attitude towards compliance with the use of masks in RW 1 Wilangan, Wilangan Village, Nganjuk Regency with a magnitude of influence of 72.4%. It is hoped that the public can comply with health protocols as they should where they must use standard masks, keep their distance and diligently wash their hands with soap. This will reduce the risk of spreading the Covid-19 virus.